THE RELATIONSHIP OF FAMILY SUPPORT ON ELDERLY DEPRESSION - Lisnawati, Lisnawati; Nazaruddin, Nazaruddin; Zoahira, Wa Ode Aisa (Nursing Genius Journal, 2024)
Background Depression in the elderly is still a health problem in Indonesia. One of the risk factors for depression is lack of family support. The aim of this research is to analyze the relationship between family support and depression in the elderly in Wanggudu Village, Asera District, North Konawe Regency. Quantitative research method with cross sectional design. Respondents were 43 elderly people who were selected using simple random sampling. Data were collected using a structured questionnaire, analyzed univariately and bivariately with the Spearman correlation test (α=0.05). Results Most of the elderly (69.7%) received insufficient family support. In addition, most elderly people (69.7%) experience severe depression. The statistical test results show an R correlation value of 0.7 and a p value = 0.000 (p<0.05), which means there is a significant relationship between family support and depression in the elderly. The lower the family support, the higher the level of depression in the elderly. Conclusion There is a significant relationship between family support and depression in the elderly. Low family support contributes to the emergence of depressive symptoms in the elderly. Increasing attention and interaction from family members is very necessary to prevent depression in the elderly.